A comparative assessment of intimate partner violence perpetration among male military personnel and civil servants in Ibadan, Nigeria - Adejimi, Adebola A. (Journal of family violence, 2022)
The mode of training and work of the military personnel is different from that of civil servants and may affect their relationships with their intimate partners. This study assessed and compared the prevalence and correlates of self-reported Intimate Partner Violence (IPV) perpetration against female partners by male military personnel and civil servants in Ibadan, south-western Nigeria. A cross sectional survey of 1240 respondents, comprising 631 military personnel and 609 civilians, was conducted using a multistage sampling technique. A self-administered questionnaire was used to collect data on the respondents’ characteristics and the different types of IPV perpetrated by them. Chi square test was used to compare the proportions of the different types of IPV perpetration and logistic regression analysis was used to determine the predictors of IPV perpetration in the two study groups. Military personnel reported significantly more IPV such as physical abuse, psychological abuse and controlling behaviors than the civil servants. Childhood exposure to inter-parental IPV and history of physical fight with another woman significantly increased the odds of perpetration of each type and any form of IPV in the two populations after controlling for other variables. Military personnel were significantly more likely to perpetrate any form of IPV than the civil servants. IPV was prevalent in both groups but was more among the military personnel. There is a need for multidisciplinary interventions such as psycho-education and conflict management skills to address violence against female intimate partners especially among the military population in Nigeria.